Inflación y crecimiento económico: determinantes del desempleo en Colombia (2010)
This work aims to establish if the unemployment rate in Colombia is determined by expected inflation and the rate of economic growth, between 2001 and 2009, assuming that economic agents have adaptive expectations, in order to determine if there is a contradistinction on the economical policy objectives, towards demonstrating if the Phillips curve is inverse or not. On the other, it analyzes if economic growth causes lower unemployment rates, testing Okun’s Law. It were used time series quarterized, where the main source of the database was Dane information, using the methodology of Johansen cointegration, estimating a vector error correction model and impulse response functions. The results show that the decreasement of unemployment rate is higher when there are increases on inflation expectation, than when there are increases on the economic growth rate